(3QSGdI aj GdCSWMIs - (3MSf Hf EHQGgje Hf MSf Hf Ydj GdRjdYj GdLHQJj GdYbjdj GdMfaj,J (B1188 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLI GYde Gf GdCSWMI HLejY CfhGY ef efMQaGJ hbGFeGJ s
(3BNQgG (B:s
(3hdfbOe Ydi cd OSJhQ MSGH eDGeQGJg dRjGOI GdEjVGM hGddg GYde s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B178 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B193s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B360 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B38 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3ejbGJ (B175) s
Keywords: (3Gdadcs